The time course of semantic richness effects in visual word recognition - Rabovsky, Milena; Sommer, Werner; Abdel Rahman, Rasha (Frontiers in Human Neuroscience, 2012)
The richness of semantic representations associated with individual words has emerged as an important variable in reading. In the present study we contrasted different measures of semantic richness and explored the time course of their influences during visual word processing as reflected in event-related brain potentials (ERPs). ERPs were recorded while participants performed a lexical decision task on visually presented words and pseudowords. For word stimuli, we orthogonally manipulated two frequently employed measures of semantic richness: The number of semantic features generated in feature-listing tasks and the number of associates based on free association norms. We did not find any influence of the number of associates. In contrast, the number of semantic features modulated ERP amplitudes at central sites starting at about 190 ms, as well as during the later N400 component over centro-parietal regions (300-500 ms). Thus, initial access to semantic representations of single words is fast and word meaning continues to modulate processing later on during reading.